Analisis Kinerja Tarif Angkutan Perkotaan Di Kota Cirebon Berdasarkan Biaya Operasi Kendaraan (Studi Kasus : Trayek D6) - Rizka, Alivina; Lestira Hariani, Mira (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2023)
The Covid 19 pandemic had an impact on the transportation sector, where the Government has placed restrictions on people's movements. This had an impact on the weakening of the passenger transportation industry as a result of the decreased number of passengers during the pandemic to post-pandemic covid 19. This study aims to determine the performance of urban transportation fares in Cirebon City, especially the D6 route with the Vehicle Operating Cost approach based on actual load factor data in the field. The method used in this study was a primary survey which included headway survey and passenger get in-get off survey. The data obtained then analyzed using the Vehicle Operating Costs approach in calculating fares to determine the suitability between the actual conditions and the operating costs that must be incurred. The results showed that under actual conditions (the highest average load factor was 45%), the existing fare of Rp.6.000/passenger was below the fare based on vehicle operating costs which resulted in a fare of Rp.8.707/passenger. In order to ensure the sustainability of urban transportation operations in Cirebon City, it is necessary to increase the number of transport passengers according to a minimum standard of 70% load factor or apply subsidies from the Government for the implementation of urban transportation.